2006
DOI: 10.1080/03610730600875759
|View full text |Cite
|
Sign up to set email alerts
|

Change in Subjective Age among Older People over an Eight-Year Follow-Up: ‘Getting Older and Feeling Younger?’

Abstract: The purpose of this prospective study was to describe changes in subjective age over an 8-year period among community-dwelling people aged 65 to 84 years in Finland. At the baseline 1155 respondents met study criteria and 451 of these participated in the follow-up study. Participants described in years the age they felt themselves to be (feel age) and their preferred age (ideal age). Discrepancy scores relative to chronological age were calculated for feel age and ideal age. No significant mean-level changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 36 publications
5
59
1
1
Order By: Relevance
“…However, given that a majority of older people report a youthful subjective age (e.g. Gana et al, 2004;Uotinen, Rantanen, Suutama, & Ruoppila, 2006), there are reasons to expect that the pattern of relationships observed in this study is likely to be generalized across a larger sample. Finally, this study used a unidimensional measure of subjective age, given that felt-age, do-age, look-age, and interest-age items were interrelated and operated statistically as a unidimensional construct.…”
mentioning
confidence: 70%
“…However, given that a majority of older people report a youthful subjective age (e.g. Gana et al, 2004;Uotinen, Rantanen, Suutama, & Ruoppila, 2006), there are reasons to expect that the pattern of relationships observed in this study is likely to be generalized across a larger sample. Finally, this study used a unidimensional measure of subjective age, given that felt-age, do-age, look-age, and interest-age items were interrelated and operated statistically as a unidimensional construct.…”
mentioning
confidence: 70%
“…Findings from longitudinal studies (e.g., Kleinspehn-Ammerlahn, Kotter-Grühn, & Smith, 2008;Sargent-Cox et al, 2012;Schafer & Shippee, 2010b;Uotinen, Rantanen, Suutama, & Ruoppila, 2006;Wurm et al, 2013) suggest that physical health and changes in physical health play an important role in developing older age identities and more negative self-perceptions of aging. When people experience health problems, they may attribute their health problems to age (rather than, for example, to lifestyle) and, hence, may start to feel older.…”
Section: The Role Of Healthmentioning
confidence: 97%
“…Essentially, primary social groups are foundational for understanding people's experiences, and it is the very durability and continuity of these relationships which make them so meaningful for people's life chances and well-being (Gecas 2003). For the current inquiry, events in the lives of significant others must 2 We have identified only one empirical article with our quantitative measure of age identity using two waves of data, but it was essentially a descriptive study of elderly Finnish adults (Uotinen et al 2006). One recent study observed a sample of 19-year-old Philadelphians over a 2-year period to see whether role and responsibility changes (e.g., starting an independent household, parenthood) elicit the subjective attainment of adulthood (Benson and Furstenberg 2007).…”
Section: Potential Influences On Age Identitymentioning
confidence: 98%